Mechanical Tuning of Through‐Molecule Conductance in a Conjugated Calix[4]pyrrole. Issue 23 (19th June 2018) - Stefani, Davide; Perrin, Mickael; Gutiérrez‐Cerón, Cristian; Aragonès, Albert C.; Labra‐Muñoz, Jacqueline; Carrasco, Rodrigo D. C.; Matsushita, Yoshitaka; Futera, Zdenek; Labuta, Jan; Ngo, Thien H.; Ariga, Katsuhiko; Díez‐Pérez, Ismael; et al.
Abstract: A conformationally flexible calix[4]pyrrole possessing a conjugated electronic structure (an N‐substituted oxoporphyrinogen (OxP) related to porphyrin) was used to investigate the influence of mechanical stretching on the single‐molecule conductance of these molecules using the mechanically‐controlled break junction (MCBJ) technique. The results show that the molecule can be immobilized in a single‐molecule break junction configuration, giving rise to different behaviours. These include step‐like features in the conductance vs. displacement traces as well as conductance traces that exhibit a slower decay ('downhill' traces) than measured for direct tunneling. The latter class of traces can be associated with the mechanical manipulation (i. e., stretching) of the molecule with inter‐electrode distances as long as 2 nm. Density functional theory (DFT) calculations reveal that OxP molecules are stable under stretching in the length regime studied. Abstract : Pulling a tetrapyrrole. A conformationally flexible calix[4]pyrrole possessing a conjugated electronic structure was used to investigate the influence of mechanical stretching on the single‐molecule conductance of these molecules using the mechanically‐controlled break junction technique.